Correlates of Safe Disposal of Children’s Stool in Nigeria: Evidence from 2018 Demographic and Health Survey - Sulaimon T. Adedokun; Amos O. Oyedokun; Olufunmilayo O. Banjo (European Scientific Journal, ESJ, 2020)
Unsafe Stool disposal has been linked to high under-five morbidity and mortality in many low and middle-income countries. This paper focuses on examining the prevalence of safe disposal of stools in Nigeria and the factors affecting such behaviour. The most-recent Nigeria Demographic and Health Survey 2018 (NDHS) Child’s dataset was used for the analysis in this study. Sample size of 7,834 children under age five was analysed. Percentages and frequencies, chi-square test of association, and binary logistic regression were employed for the statistical analysis. Findings show that a little above half of the women respondents reported safe disposal of stool of their under-five children in the study area (53%). Specifically, the odds of having stool safely disposed increased by 133 percent for children whose household wealth index falls within the richer category (adjusted Odd Ratio (aOR): 2.33; p<0.001), reduced by 17 percent for children whose mothers are working (aOR: 0.83; p<0.05), increased for children whose mothers are residing only in North-East and North-West (p<0.001), increased by 19 percent for children whose mothers were exposed to media exposure to mass media (aOR: 1.19; p<0.05), reduced by 24 percent for women whose children are of first birth order (aOR: 0.76; p<0.05), reduced by 31 percent for women whose children are of small size at birth (aOR: 0.69; p<0.001), increased by 66 percent for women who reported that distance to facility was not a problem (aOR: 1.66; p<0.001), reduced by 19 percent for women who delivered their children at an health centre (aOR: 0.81; p<0.05), and increased by 114 percent for women who used improved toilet facility (aOR: 2.14; p<0.001). This study concludes that a combination of socioeconomic, maternal, child’s and environmental factors are the correlates of safe disposal of stool among women with under-five children in Nigeria. It should therefore be prioritised for interventions aimed at reducing high under-five morbidity and mortality in Nigeria.